Redesign Kemasan Keripik Singkong Menggunakan Kansei Engineering - Dermawan, Dedi; Qurthuby, Muhammad; Denur, Denur; Ali Ardi, Hendri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Cassava chips are snacks processed from cassava that is thinly sliced and fried and chip is a snack that is familiar to the public and everyone likes it in the home industry, savory cassava chips cap elang production But in this home industry has several problems, namely how to attract new consumers to buy this savory eagle cap cassava chip product. So one of the efforts that can be done is to innovate the design on the packaging to make it more attractive. The method used in innovating this packaging design is by kansei engineering. The goal to be achieved in this study is to identify the packaging design specifications desired by consumers and provide new packaging design proposals. Some of the stages carried out in this kansei engineering method are by collecting kansei words, validity and reliability tests, factor analysis, determining design elements, conjoint analysis,. From the results of data processing, the results of the packaging design desired by respondents were made of plastic, in the form of a standing pouch, having a distinctive patterned design and a light color.